The Impact of Price, Product Quality, and Location on Pur-chasing Interest in Choosing a Complete Supermarket as a Place to Shop for Baby and Household Supplies - Ali Sodikin; Miftahurrohman Miftahurrohman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research goals to investigate and prove the impact of Price, Product Quality, and Location on Purchasing Interest in choosing Complete Supermarket as a place to shop for baby and household supplies. Purchasing interest is a crucial element that determines the accomplishment of a retail business, and is impactd by various marketing elements. This study employs a descriptive quantitative approach with a study framework. The population in the research is consumers of Complete Self-Utility. Sampling was carried out using certain techniques (for example, Purposive Sampling or Simple Random Sampling) with a total of 100 respondents. Data were collected through questionnaire deployment and looked over using multiple linear regression analysis. The outcome of the research are expected to reveal that: (1) Price has a positive and substantial effect on Purchasing Interest; (2) Product Quality has a positive and substantial effect on Purchasing Interest; (3) The location has a positive and substantial effect on the Purchasing Interest; and (4) Price, Product Quality, and Location simultaneously have a substantial effect on purchasing Interest.